Agricultural Intensification, Diversification and Migration as Livelihood Strategies Among Rural Scheduled Tribe Population of Palasbari Revenue Circle: A Case of India - Das, Meghna; Gogoi , Barnali (Asian Journal of Agriculture and Rural Development, 2020)
The key objective of this study is to examine the livelihood practices and strategies adopted by the Scheduled Tribe (ST) population of the Palasbari Revenue circle, Assam, India. For empirical analysis, 132 households were surveyed from 6 areas dominated by the ST population, namely Kallapara N.C. (Satargaon), Jimirigaon, Rani Khamar, Chouthala, Jupangbari, and Kochpara, which aggregates to 553 sample populations. It was surveyed by stratified random sampling method from January to March 2020. The results show that livelihood diversification, agricultural intensification and temporal migration are three of the major strategies adopted by the population to meet their needs.